High-dose edible bird’s nest extract (EBN) upregulates LDL-R via suppression of HMGCR gene expression in HepG2 cell lines - Mohd Noor Akmal; Intan-Shameha Abdul Razak; Rozaihan Mansor; Aini Ideris; Abdul Rahman Omar; Jalila Abu; Mokrish Ajat (Penerbit Universiti Kebangsaan Malaysia, 2020)
Edible bird’s nest (EBN) is an ancient food that had been consumed by Chinese people for well-being purposes. Nevertheless, the effect of EBN on cholesterol metabolism is poorly studied. Since the cholesterol is primarily being metabolized in the liver, HepG2 cell lines was selected as the model for in-vitro preliminary assessment. Our EBN extract (EBNE) showed 71% cell viability in HepG2 cell lines, even at the highest dose (1.5 mg/mL). Simultaneously, EBNE was significantly up-regulated the LDL-R gene expression via suppression of HMGCR at the highest concentration. Besides that, ACAT2 was up-regulated significantly to allow exogenous cholesterol storage. Expression analysis of these genes were correlated with high immunofluorescence distribution of the LDL-R and LDs compared to other treatment groups. Consistent with gene expression and immunofluorescence staining, intrahepatocellular cholesterol concentration was increased significantly at the highest dose of EBNE. The EBNE had significantly improved cholesterol metabolism in the HepG2 cell line via suppression of the HMGCR gene and subsequently up-regulated LDL-R gene expression at the highest dose. Therefore, this study provides an insight to understand the effect of EBNE in improving cholesterol metabolism.